Phenolic Compounds from Water-Ethanol Extracts of Tetrapleura tetraptera Produced in Cameroon, as Potential Protectors against In Vivo CCl4-Induced Liver Injuries - Peter William Kemewele Saague; Bruno Moukette Moukette; Jacques Romain Njimou; Prosper Cabral Nya Biapa; Francine Nzufo Tankeu; Vicky Joseline Ama Moor; Constant Anatole Pieme; Jeanne Yonkeu Ngogang (The Scientific World Journal)
Background. Liver diseases are a global health problem. Medicinal plants are being increasingly used to manage a wide variety of diseases including liver disorders. The aim of this study was to investigate the antioxidant properties and hepatoprotective activity of polyphenolic extract from the fruits of Tetrapleura tetraptera (T. tetraptera). Results. The extract of T. tetraptera was administered at doses of 50 mg/kg and 100 mg/kg for 07 per os to rats before the induction of hepatotoxicity with of 2 ml/kg of 1:1 (v/v) carbon tetrachloride (CCl4) and olive oil through intraperitoneal route. The in vitro antioxidant and radical scavenging properties of T. tetraptera were conducted by the FRAP method, the phosphomolybdate method, and the inhibition potential of DPPH, ABTS, OH, and NO radicals. The extraction yield of T. tetraptera was 19.35%. This extract contains polyphenols (273.48 mg CAE/g DM), flavonoids (5.2549 mg SE/g DM), and flavonols (1.615 mg SE/g DM). This extract showed in vitro antioxidant activity, an inhibitor power of various free radicals, and radical scavenging potential dose-dependent. The fifty-percent inhibitory concentration of the extract (IC50) for the studied radical varied from 28.16 to 136 μg/L. In rats treated with the extract of T. tetraptera, in a dose-dependent manner, the levels of hepatotoxicity markers such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) significantly increased while the enzyme activities of superoxide dismutase (SOD), catalase (CAT), and the level of reduced glutathione (GHS) significantly increased compared to the control group. Conclusions. The extracts from the fruit of T. tetraptera demonstrate antioxidant activity and hepatoprotective effects.